Diabetes Mellitus and Oral Health Status: A Case-Control Study in a Tertiary Care Hospital in Bangladesh (Update Dental College Journal, 2024)
Introduction: Diabetes is a long-lasting, inflammation-related metabolic disorder which is diagnosed by hyperglycemia. Increased blood glucose level adversely impacts the inflammatory response to periodontium leading to more severe gingivitis and periodontitis. Therefore, periodontitis and diabetes reciprocally and adversely affect each other.Objective: To assess and compare the oral health condition of Diabetic and non-Diabetic patients. Method: A case control study was conducted among 100 diabetic and 100 non-diabetic patients. The control group was matched by age and gender. The study was conducted for a period of ten months. A cheek list was prepared to generate the caries and CPITN index (Community Periodontal Index of Treatment Needs) index.Result: Dental caries scored at least one was relatively more in non-diabetics (32%) than in diabetics (24%). However, the periodontal diseases (pyorrhea) was more in diabetic patients (89%) in compared to non-diabetics (62%). The odds ratio for CPITN Index indicated that the patients who had periodontitis were about 24 times (OR = 24.00, 95% CI 8.19- 70.26) more likely to have diabetes.Conclusion: Diabetes is a major issue in oral health care. The evidence also recommends that oral health care providers can have a significant role to provide an operational and progressive effect on the oral health with diabetes mellitus.Update Dent. Coll. j: 2024; 14(1):10-14